Penerapan metode bernyanyi terhadap kemampuan mencuci tangan pada anak usia pra sekolah - Fitri, Feni Elda; Nurhayati, Nurhayati; Ningsih, Tri Riwayati (THE JOURNAL OF Nursing Management Issues, 2024)
Background: Preschoolers aged 3-6 years are experiencing a crucial period that lays the foundation for their future development. Handwashing is the process of vigorously rubbing both surfaces of the hands together using an appropriate substance and rinsing with water. Purpose: To eliminate as many microorganisms as possible, it also reveals that handwashing (also considered hand hygiene) is essential. Method: Descriptive research using a case study method. Results: The effect of the singing method on handwashing skills in preschool-aged children was found to have an impact on children's abilities before and after being exposed to the singing method. Results: The effect of the singing method on handwashing skills in preschool-aged children was found to have an impact on children's abilities before and after being exposed to the singing method. Conclusion: Before the implementation, Subjects 1 and 2 were unable to perform the six steps of handwashing correctly. After five days of implementation, changes were observed in Subjects 1 and 2's ability to perform the six steps of handwashing correctly without assistance. Recommendation: Health workers should provide counseling on the implementation of the singing method to improve handwashing skills in preschool-aged children. It is hoped that respondents will understand the benefits of implementing the health education activities provided.   Keywords: Handwashing skills; Literature; Preschool-aged children; Singing method.   Pendahuluan: Anak usia prasekolah adalah anak yang berusia 3-6 tahun dimana anak mengalami masa yang sangat penting sebagai pondasi atau dasar untuk perkembangan masa depannya. Mencuci tangan adalah proses menggosok kedua permukaan tangan dengan kuat secara bersamaan menggunakan zat yang sesuai dan dibilas dengan air. Tujuan: Untuk menghilangkan mikroorganisme sebanyak mungkin juga mengungkapkan bahwa cuci tangan (juga dianggap hygiene tangan) Metode: Penelitian deskriptif dengan menggunakan metode studi kasus. Hasil: Metode bernyanyi terhadap kemampuan mencuci tangan pada anak usia pra sekolah ditemukan adanya kemampuan anak sebelum dan sesudah diberikan penerapan metode bernyanyi terhadap kemampuan mencuci tangan. Simpulan: Sebelum diberikan penerapan pada subjek 1 dan subjek 2 belum mampu melakukan 6 langkah cara mencuci tangan dengan baik dan benar. Setelah diberikan penerapan selama 5 hari di dapatkan perubahan kemapuan subjek 1 dan 2 mampu melakukan 6 langkah cara mencuci tangan dengan baik dan benar tanpa bantuan orang lain. Saran: Tenaga kesehatan mampu memberikan penyuluhan tentang penerapan metode bernyanyi untuk meningkatkan kemampuan mencuci tangan pada anak usia pra sekolah, diharapkan responden memahami manfaat penerapan kegiatan pendidikan kesehatan yang diberikan.   Kata Kunci: Anak Usia Pra Sekolah Kepustakaan; Kemampuan Mencuci Tangan; Metode Bernyanyi.